Video Observed Treatment is an Innovative Method of Tuberculosis Treatment Observation in Resource-Limited Health Care Settings - N. A. Pavlyuchenkova; I. A. Vasilyeva; A. G. Samoylova; T. E. Tyulkova (Туберкулез и болезни лёгких)
The objective of the study: to analyze the potential use of video observed therapy (VOT) as one of the fields of mobile health care for treatment of patients with tuberculosis, to substantiate prospects of using VOT as an alternative to directly observed therapy including settings with limited health care resources.Subjects and Methods. The relevant studies were searched for in the following bibliographic databases: MEDLINE/PubMed, EMBASE, LILACS, IMEMR and IMSEAR, and clinicaltrials.gov. 40 publications devoted to video observed treatment of tuberculosis abroad and in Russia were selected. The recommendations of the World Health Organization on the use of digital technology in tuberculosis treatment, in particular video observed treatment have been studied.Results. The article highlights the advantages of video observed treatment of tuberculosis, the possibility of implementing this approach in different groups of patients taking into account the inclusion and exclusion criteria, assessing effectiveness of its use (improved treatment adherence, higher number of completed observations, better responsibility of patients for the disease and therapy, economic benefits for the health system and the patient). The study speculates on the potential implementation of video observed therapy of tuberculosis in the Russian Federation.